LEASING CHARACTERISTICS AND THE ANALYSIS OF THE LESSOR – LESSEE RELATIONSHIP - GEORGESCU MARIA – ANDRADA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2010)
Even if leasing is a form of financing whose use is quite widely spread, it must be exercised in a precise legislative framework. Thus, we will present the nature of the leasing operation and the framework for exercising it. Secondly, we will treat the obligations derived from the tripartite transaction between the lessee enterprise, the supplier and the leasing company, as obligations that, through their observing, determine the validation of the financing agreement. More precisely, the relation between the lessor and lessee will be analyzed as an agent relationship; the existence of deviating behaviours of the lessee will bring forth agent costs. Thirdly, we will approach different mechanisms that allow the solving of the agent conflicts.